Using customer relationship management systems at university libraries: A comparative study between Saudi Arabia and Egypt. (June 2017) - Fouad, Nehal; Al-Goblan, Najah
Today, libraries stand in a difficult position that requires exerting efforts to prove their competitive abilities for attracting and satisfying their customers in a virtual environment that has various sources of information. This requires libraries to pay great attention to promoting customer relationship management with their customers for their knowledge development goal plans and strategies to achieve success amidst the current competitive circumstances. The current study aims at surveying the potential implementation of customer relationship management systems in university libraries. This happens through the introduction of the customer relationship management concept to university libraries, the implementation mechanisms of these systems, and the level of the libraries' tendency to adopt them. In addition, the current study surveys the obstacles that confront customer relationship management systems usage in university libraries in Saudi Arabia and Egypt.